Orientasi kewirausahaan sebagai mediasi faktor demografis terhadap kinerja bisnis - Iva Nurdiana Nurfarida; Endi Sarwoko (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
Extant literatures suggest that personal characteristics of entrepreneurs have a large impact on a business performance. The Resource Based View, regards the characteristics of the entrepreneur as a unique resource for the company that will become a competitive advantage. So far, personal characteristics and entrepreneurial demographic factors are more associated with entrepreneurial intentions, this study will analyze the role of demographic factors, namely educational background, family, experience, and motivation on a business performance, while also examining the role of entrepreneurial orientation, namely innovation, proactivity, and risk taking in mediating these effects. The research sample consisted of owners/managers from 160 business units in Malang area (Malang City, Batu, and Malang Regency), while the data analysis technique used Structural Equation Modeling (SEM). The results showed that demographic factors influence business performance and entrepreneurial orientation, so educational background, family background, business experience, and motivation are determinants of a business performance while enhancing entrepreneurial orientation. Entrepreneurial orientation acts as a mediator of demographic factors affecting business performance.